Indonesia Young Generation Appreciation Towards Korean Popular Music (K-Pop) - Ivadaputra, M. Firdaus; Rudito, Bambang (Journal of Business and Management, 2013)
At the beginning of the second decade in the 21st century, K-Pop which part of the Korean Wave (Hallyu) has managed to achieve success flapping wings to foreign countries. Indonesia is one country that is affected by the presence of K-Pop music. K-Pop music influences in Indonesia that occur are marked by numerous musical concerts which held by Korean boyband and girlband. Likewise the emergence of new boyband and girlband from Indonesia who are follow K-Pop musical style. Indonesia's young generation is now being hit by K-Pop fever. The research is conducted to capture a phenomenon of K-Pop culture by young generation in Bandung which expected to represent Indonesia in general. The studies illustrate several aspects: the background of K-Pop could become a trend among the younger generation, identifying the role of media in spreading K-Pop music, as well as the culture that appeared among K-Pop fans. Various kinds of appreciation are made by young generation towards K-Pop so it emerges a new habit among K-Pop fans. Results indicate three aspects of research that can make a successful K-Pop captivate Indonesia young generation, specifically in terms of content, delivery, and the behavior of K-Pop consumer itself. In terms of content, K-Pop are adored because of artist physical appearance, music, and choreography which is exciting and has typical features. In terms of delivery, K-Pop which is dependence on the Internet and advances in information technology make K-Pop easily and quickly spread. In terms of fan behavior, they are always well appreciated and very loyal with their craze. K-Pop having some effects of positive but also negative for Indonesian people especially among teenagers. It is so easy for Indonesian people society to accept foreign cultures which can actually shift the original Indonesian culture. The entry of foreign culture into a country is actually reasonable as long as the cultural in line with the personality of the nations. However, we have to keep on maintaining the culture in order to keep our culture not fade away.Â Keywords: K-Pop, young generation, popular culture, internet media----------------DISCLAMER: This paper is created by undergraduate students of School of Business and Management ITB in partial fulfillment of the requirement of the degree Bachelor of Management. Journal of Business and Management is not responsible for the content, opinions, or any other materials expressed here.